Global HIV/AIDS Monitoring and Evaluation Team in the MAP Projects (GAMET) - Watkins, Sharon (World Bank, Washington, DC, 2012)
The Global HIV/AIDS Monitoring and Evaluation Support Team (GAMET) was formed in July 2002 as a unit of the Bank's Global HIV/AIDS Program in the HDN Vice Presidency. Its aim is to work with countries globally to strengthen and develop their capacity to monitor and evaluate the results of national programs and policy on HIV/AIDS. GAMET was created as a partnership between UNAIDS, other UN agencies, the Bank, the Global Fund for AIDS, Tuberculosis, and Malaria (GFATM), and several technical agencies including the Global Program on HIV/AIDS, and the MEASURE/Evaluation project. It is funded by the UNAIDS trust fund for GAMET operations and by the Bank. The GAMET Country Support Team (CST) consists of 17 international Monitoring and Evaluation specialists who work in collaboration with the national M&E teams. The broad development objectives of GAMET are to utilize the principles and practice of M&E to build country capacity and mitigate the problems associated with HIV/AIDS. This includes three central objectives; i) innovation and development of strategies that incorporate M&E into the framework of the MAP projects ii) country assistance in their initiation of a national framework for M&E and the development of success indicators, and iii) the creation of community-level activities that are able to help local managers accurately assess program interventions.